Decreased Expression of TGR5 in Vogt-Koyanagi-Harada (VKH) Disease. (17th February 2020) - Yang, Jinglu; Hu, Jianping; Feng, Lujia; Yi, Shenglan; Ye, Zi; Lin, Meng; Liu, Xinglan; Pu, Yanyu; Kijlstra, Aize; Yang, Peizeng; Li, Hong
ABSTRACT: Purpose : To investigate the role of G-protein-coupled bile acid receptor-1, Gpbar1 (TGR5) in the pathogenesis of Vogt-Koyanagi-Harada (VKH) disease. Methods : The mRNA level of TGR5, iNOS, Arg1, CD16, and CD206 in macrophages was assayed by real-time PCR. ELISA was used to detect the production of cytokines in cell culture supernatants. The frequencies of CD4 + IFN-γ + and CD4 + IL-17 + T cells were tested by flow cytometry. Results : A decreased expression of TGR5 in M1 macrophages was observed in active VKH patients as compared with normal controls. TGR5 stimulation of M1 macrophages with INT-777 caused a shift of the inflammatory M1 toward the anti-inflammatory M2 macrophage subtype. TGR5 activation of macrophages co-cultured with CD4 + T cells inhibited Th1 and Th17 polarization, as well as the release of IFN-γ and IL-17 in the culture supernatant. Conclusion : Our results show that a decreased TGR5 expression might contribute to the pathogenesis of VKH disease.